Dispositional Instruments of Protection against Administrative Acts (not in Legal Force) and their Effectiveness - Stanislav Kadečka; David Hejč; Klára Prokopová; Jiří Venclíček (Central European Public Administration Review)
Public administration is often implemented through the issuing of public acts of a unilateral and binding character. Within public administration, however, legal instruments by which those for whom the administrative acts are binding can defend themselves against any illegality or irregularity of the mentioned administrative acts, are also (must be) provided. The existence and proper effectiveness of these legal instruments can be regarded as a necessary part (sine qua non) of the democratic rule of law. The paper is concerned with the so-called dispositional legal instruments of protection against the administrative acts which are not yet in legal force and their effectiveness. Article's major finding consists in fact, that the effectiveness of dispositional instruments of protection could be limited by absence of devolutive effect, or guarantee of independence in organizational arrangement between first and second instance administrative bodies.